Pengaruh Konsep Gamifikasi Terhadap Tingkat Engagement - Pratomo, Aditya (THE Journal : Tourism and Hospitality Essentials Journal, 2018)
The survey results conducted Director of Learning, engagement level for leaders The Park Lane Jakarta is quite a low of 23% when engagement leaders low then it is likely his engagement will be the same. Then with the implementation of the concept of gamification is expected to enhance the engagement of employees towards learning. Type of this research is descriptive research with survey method. To the object of research is the hotel The Park Lane Jakarta. The independent variable is the influence of the concept of the dependent variable and the gamification is the engagement of employees. For a data source used is the primary and secondary data of a population of 269 and value precision of 10%. Based on the results of research that the concept of gamification gives a significant impact on employee engagement, there is 38.4% against employee engagement. As well as according to hypothesisÂ testing is evidenced by the receipt of the Ha and turned it on test of the Ho hypothesis.